ANALISIS PROSEDUR SYARAT PENCALONAN GUBERNUR DAN WAKIL GUBERNUR LAMPUNG TAHUN 2018 (Studi di Komisi Pemilihan Umum Provinsi Lampung) - S. ENDANG PRASETYAWATI (KEADILAN PROGRESIF, 2018)
Pemilukada as the local elections mechanism directly by the people in the region, the Lampung Provincial Election Commission as the organizer of Pemilukada contribute to the success of substantial and quality democracy related to the procedure of candidacy for governor and deputy governor in Lampung Province 2018. The research problem is: conditions governor candidacy and vice governor of Lampung Year 2018.Juridical normative and empirical research methods, using primary and secondary data, and data analysis with qualitative analysis. The results of the Procedures of Governor and Vice Governor Candidate Requirements Candidates include Candidate Pairs Registration, Campaign Period, Report and Audit of Campaign Funds and Collection and Counting as stipulated in Law Number 10 Year 2016 and Regulation of KPU Number 3 Year 2017 on the Candidate Candidate of Governor and Vice Governor Election , Bupati and Deputy Regent, and / or Mayor and Deputy Mayor. Suggestions that can be given by the writer, among others, The selection of local head directly by the voting community is expected to run according to the stages determined and implemented by Provincial KPU and Regency /